Visualizing Imagery of Poetry Because I Could Not Stop For Death by Emily Dickinson - Santini, Ni Komang Ayu Melly; I Nengah , Sudipa; Ni Luh Putu , Krisnawati (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
This study article analyzed visual imagery of poetry “Because I Could Not Stop For Death” by Emily Dickinson. The aim of this article is analyzing the visual imagery in the poetry.  This article presented the data by using descriptive qualitative method with the theory from Pradopo (2009) in analyzing the visual imagery. There are some steps in conducting this study. First step is by selecting the poetry, analyze the word or phrase that is related with the visual imagery, and then analyze the data. The data are taken from the internet. The focus of this study is on the visual imagery and it would differentiate this article from the previous article. The findings of this article showed seven visual imagery of the phrase or line found in the poetry “Because I Could Not Stop for Death” by Emily Dickinson. Most of those phrases show visual imagery of natural beauty and scenes from places that are being observed as symbolism of life stages. The speaker conveyed the sense of sight by using figurative language.